TRANSITION SIGNAL BETWEEN ARTICLES AND SHORT STORIES: A COMPARATIVE STUDY - Aditya, silvia Erlin; Topa, Romadi (LITERARY CRITICISM, 2014)
This study investigated the transition signals appeared in education articles of Edarticle and short stories of O.Henry. The objectives of the study were to find out the types of transition signals, the frequency of each transition type, the diffrencesÂ of those that were used in education articles of edarticle and short stories of O.Henry. The population of this study are two articles and two short stories and all of them were selected as the sample. The data were collected by using primary data, the secondary data, and data analyzing technique is descriptive qualitative. The data were gathered by identifying the transition signals which inherent with Oshima and Hogueâs theories. The data were classified into three classification following theory; in which transition signals classified into connectors, coordinators, and subordinator. The result of this study show coordinators frequently used (93 items in articles and 132 items in short stories), the second was subordinators (35 items in articles and 38 items in short stories), and last was connectors ( 28 items in articles and 18 items in short stories).Â A suggestion was transition signals in any kind of hand writing (fiction or non fiction) can help reader to understand and to follow what writerâs thought. Keywords: transition signals, article of edarticle, short story.